National Structure And Number Of The Population Of Zarafshan District: Historical And Source Analysis (Eurasian Journal of Humanities and Social Sciences, 2022)
This article deals with the national composition, number and other characteristics of the population of Zarafshan district, which was a special administrative-territorial unit of the Governor-Generalship of Turkestan. To shed light on the problem, a historicalsource analysis of written sources, archival materials, research, and historical literature involved in the research process was conducted.